Characterization and functional analysis of non-ribosomal peptide synthetase in Ganoderma boninense PAT - Shokrollahi, Neda (2021)
Basal stem rot (BSR) is a destructive disease caused by a white-rot fungus, Ganoderma boninense Pat. which has threatened the oil palm industry for more than eight decades without any effective treatment available until now. Therefore, it is crucial to understand the role of non-ribosomal peptides (NRPs) implicated as virulence factors during pathogenesis particularly in Ganoderma-oil palm pathosystem where this information is lacking. The objectives of this study were i) to isolate NRPS gene of G. boninense strain UPMGB001 using PCR-based method, to analyze the sequence with bioinformatics tools, namely antiSMASH and Augustus, also the prediction of the secondary structures and three-dimensional structure modelling of the polypeptides by using SOPMA and the SWISS-MODEL tools, respectively; ii) to analyze the secondary metabolite(s) related to NRPS released by G. boninense during its interaction with oil palm in vitro by using Liquid Chromatography Triple Quadrupole Mass Spectrometer (LC-MS/MS) and performance liquid chromatography (HPLC) by using analytical standard; and iii) Expression of G. boninense NRPS gene and its correlation with basal stem rot disease severity in oil palm seedlings by performing quantitative real-time PCR (qPCR), finally to investigate the correlation between disease severity and NRPS expression within six months. The isolated NRPS fragment of 8,322 bp was used to predict the putative peptide sequence of different domains and showed similarity with NRPS adenylation domain (core motifs of A1 and A10), thiolation and condensation domains. Furthermore, phylogenetic analysis of NRPS sequences demonstrated that NRPS of G. boninense belongs to the type VI siderophore family. Ricinoleic acid was detected in the culture filtrate that was produced by G. boninense strain UPMGB001 during the pathogenicity in oil palm in vitro while this compound was not detected in the control sample. It was the first report on ricinoleic acid synthesis by G. boninense that was confirmed by using HPLC and ricinoleic acid analytic standard. The correlation between high disease severity (50%) and high expression (227 fold change) of G. boninense NRPS gene at 4 months after inoculation and above indicated that this gene played a significant role in the advancement of BSR disease. These results showed that the NRPS gene probably plays an imperative role in the development of BSR disease. These findings are new perspectives for the understanding of the functional role of NRPS of G. boninense, and they will contribute to the development of an early detection system using the NRPS region as a Ganoderma-specific biomarker for more efficient management of BSR disease in oil palm.